Experience of families of children and adolescents submitted to Hematopoietic Stem Cell Transplantation - Verônica de Azevedo Mazza; Claudia de Souza; Aline Rigo Estevão; Sérgio Luídes Guimarães; Nen Nalú Alves das Mercês (Universidade Federal de Goias, 2016)
A descriptive study with a qualitative approach to describe how families of children and adolescents submitted to Hematopoietic Stem Cell Transplantation went through this experience. We conducted semi-structured interviews with 16 relatives of children and adolescents submitted to transplantation between December of 2014 to March of 2015 at the bone marrow transplantation service at a university hospital located at the South of Brazil. We analyzed the data with steps described by Creswell, with the support of the software IRAMUTEQ. From this analysis, the emerging categories were: the mother as an active subject in the transplantation process; family experience with the transplantation; transplantation impact for the child and/or adolescent; and, transplantation: from fear to hope. Considering our results, it is possible to ponderate about the care provided by the nursing team, becoming indispensable for these professionals to plan assistance focused not only on the patient but the whole family nucleus.